Effectiveness of Natural Science Teaching: How to Implement Effective Natural Science Teaching Strategies into Basic Education Especially Fifth Grade? - Edviges Maria Sidalia de Oliveira (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2026)
This study aims to examine the teaching effectiveness of natural science teachers in basic education, particularly for grade five (5), using a new learning paradigm that aligns with the 2014 national curriculum for basic education. The researcher conducted this research at the fifth-grade primary schools of Central, Catholic Primary Schools of Saint Domingos Sávio, and CAFE School. This study employed a qualitative research method, utilizing a descriptive approach. Which present description related to the data. The data collection method involved interviews and observations related to natural science teaching strategies and their implementation in basic education. The subject that involved were science teachers and students ‘from five grades. The sampling technique used was purposive sampling. The study employs thematic analysis as the data analysis method. The research results indicated that fifth-grade teachers have implemented learner-centred strategies; however, their implementation is not perfect. Nevertheless, this approach is effective because it enhances children's learning in science and boosts their understanding and scientific self-empowerment